Sulfanilamide in solution and liposome vesicles; in vitro release and UV-stability studies - Sanja Petrović; Ana Tačić; Saša Savić; Vesna Nikolić; Ljubiša Nikolić; Sanela Savić (Elsevier, 2017)
The main goal of this study was to develop a liposome formulation with sulfanilamide and to investigate the liposomes impact on its release and stability to the UV-A/UV-B and UV-C irradiation. Liposome dispersions with incorporated sulfanilamide were prepared by thin-film hydration method and liposomes role to the sulfanilamide release was investigated by using a dialysis method. Comparatively, sulfanilamide in phosphate buffer solution was subject to release study as well to the UV irradiation providing for the possibilities of kinetics analysis. In vitro drug release study demonstrated that 20% of sulfanilamide was released from liposomes within 1 h that is approximately twice as slower as in the case of dissolved sulfanilamide in phosphate buffer solution. The kinetic release process can be described by Korsmeyer-Peppas model and according to the value of diffusion release exponent it can be concluded that drug release mechanism is based on the phenomenon of diffusion. The sulfanilamide degradation in phosphate buffer solution and liposomes is related to the formation of UV-induced degradation products that are identified by UHPLC/MS analysis as: sulfanilic acid, aniline and benzidine. The UV-induced sulfanilamide degradation in the phosphate buffer solution and liposome vesicles fits the first- order kinetic model. The degradation rate constants are dependent on the involved UV photons energy input as well as sulfanilamide microenvironment. Liposome microenvironment provides better irradiation sulfanilamide stability. The obtained results suggest that liposomes might be promising carriers for delayed sulfanilamide delivery and may serve as a basis for further research. Keywords: Sulfanilamide, Liposomes, Stability, Irradiation, Degradation, Release